2004
DOI: 10.1542/peds.2003-0280-l
|View full text |Cite
|
Sign up to set email alerts
|

Time in Continuity Clinic as a Predictor of Continuity of Care for Pediatric Residents

Abstract: Increasing time spent in clinic improves continuity and may indeed enhance the quality of this fundamental experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…This finding raises potentially important questions about the importance of including families in resident evaluations and whether faculty feedback can serve as a surrogate for ratings directly from families. 6 Whereas most pediatric medical care and a significant amount of residency training occur in outpatient settings, 10 the study by Brinkman et al 6 involved only evaluation of inpatient care. The assessment of resident professionalism, communication, and interpersonal skills in these 2 settings may be different.…”
Section: Resultsmentioning
confidence: 99%
“…This finding raises potentially important questions about the importance of including families in resident evaluations and whether faculty feedback can serve as a surrogate for ratings directly from families. 6 Whereas most pediatric medical care and a significant amount of residency training occur in outpatient settings, 10 the study by Brinkman et al 6 involved only evaluation of inpatient care. The assessment of resident professionalism, communication, and interpersonal skills in these 2 settings may be different.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 PHY is the percentage of visits in which residents see their own patients. Thus, PHY reflects continuity from the perspective of the provider and is appropriate for evaluating the educational experience of residents.…”
Section: Workload and Continuity Variablesmentioning
confidence: 99%
“…6,8 Despite its importance, studies documenting resident continuity with patients generally illustrate disappointing findings. [18][19][20][21] One study found that pediatrics patients assigned to a resident physician saw their primary physician at only 25% of their visits. 22 Although past studies have demonstrated varied levels of continuity in resident teaching practices, factors that may improve continuity have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%